Mechanisms of moral disconnection and its relationship with empathy and prosociality in adolescents who have had criminal experiences - Gómez Tabares, Anyerson Stiths (2019)
We sought to identify the relationship between the mechanisms of moral disconnection, empathy and prosociality in adolescents who have had criminal experiences. A sample of 60 adolescents between 16 and 18 years old answered the moral disconnection questionnaire (MMD), the prosocial tendency scale (PTM-R) and the emotional reactivity index (IRI). The moral disconnection mechanism with the highest score was moral justification. Moral disconnection negatively correlated with prosocial behaviors and empathy. Women presented higher means in the dimensions of empathy and prosociality, while men showed higher means in the mechanisms of moral disconnection. The study concludes that it is important to generate strategies that stimulate empathy, solidarity, emotional education and prosocial moral criteria in adolescents who break the law.